1989
DOI: 10.1159/000199897
|View full text |Cite
|
Sign up to set email alerts
|

Interdigestive Gastroduodenal Motility in Patients with Active and Inactive Duodenal Ulcer Disease

Abstract: The interdigestive gastroduodenal motility was studied by means of a manometric probe in 6 patients with active duodenal ulcer and acid hypersecretion, in 6 patients with ulcer disease in remission (inactive) and normosecretion and in 8 healthy subjects with normosecretion. After a basal recording period sufficient to record at least two activity fronts of the migrating motor complex (MMC), an intraluminal infusion of isotonic NaHCO3 was carried out for 180 min in patients with active duodenal ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…It has been proposed that the regularity of the MMC may be governed by duodenal acidity; an alkaline duodenal pH is important for initiation of gastric phase III complexes 33. The short duration of fasting recording performed in this study (30 minutes) is a potential limitation; however, inhibition of gastric acid secretion has been observed to cause an increase in fasting gastric phase III activity in other studies with ranitidine34 and omeprazole35with more prolonged recording times. Conversely, increased gastric acid secretion has been associated with a decreased occurrence of MMCs 36…”
Section: Discussionmentioning
confidence: 66%
“…It has been proposed that the regularity of the MMC may be governed by duodenal acidity; an alkaline duodenal pH is important for initiation of gastric phase III complexes 33. The short duration of fasting recording performed in this study (30 minutes) is a potential limitation; however, inhibition of gastric acid secretion has been observed to cause an increase in fasting gastric phase III activity in other studies with ranitidine34 and omeprazole35with more prolonged recording times. Conversely, increased gastric acid secretion has been associated with a decreased occurrence of MMCs 36…”
Section: Discussionmentioning
confidence: 66%
“…Intraluminal pH seems to be involved in regulating interdigestive antroduodenal motility 11 , . 12 , 14 , 16 During phases I and II of the MMC duodenal pH is always in the neutral or alkaline range. Only during phase II does the duodenal pH fluctuate irregularly between 2 and 7 11 , .…”
Section: Discussionmentioning
confidence: 99%
“… 12 Duodenal acidification inhibits gastric motility, increases irregular motor activity in the proximal duodenum and may even induce duodenal phase III‐like complexes 12 , . 13 In patients with active duodenal ulcer disease, 14 –16 and in healthy subjects with pharmacologically induced gastric hypersecretion, 14 antral motility is reduced and MMC cycle length is increased because of prolonged duodenal phase II activity. These inhibitory effects of excessive gastric acid on antroduodenal motility are reversed during gastric acid suppression using H 2 ‐receptor antagonists or by intragastric infusion of bicarbonate 15 , .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results we can conclude that duodenal acidification causes relaxation of the proximal stomach. Previous studies in humans have shown the importance of duodenal pH in the regulation of interdigestive gastrointestinal motility 22 –28 . Duodenal acidification inhibits gastric activity by decreasing the antral phase III occurrence rate, while alkalization of the duodenum increases antral phase III occurrence rate 22 .…”
Section: Discussionmentioning
confidence: 98%